Pengaruh Sosial Media Instagram terhadap Keputusan Menginap di The Jayakarta Bali Beach Resort & Spa - Putu Ricky Danendra; I Nyoman Sukana Sabudi; Prastha Adyatma; Ni Desak Made Santi Diwyarthi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Social media also uses stimuli to influence customer perceptions and behavior. Therefore, companies use it as a strategic tool to develop strategies to enhance their corporate image, brand loyalty, brand awareness, brand equity, and brand sustainability. Currently, companies predominantly build their social media sites and share interesting information about their products to raise awareness and improve brand-building effectiveness and customer acquisition. Social media has become an important and easy platform for delivering information to the public. In this context, The Jayakarta Hotel has followed the promotional trend through digital marketing. The method used in this study is a quantitative method with a descriptive quantitative approach. Data collection was carried out by distributing an online questionnaire using Google Forms to 115 respondents. The method used in this research is purposive sampling. The data analysis techniques employed include simple linear regression analysis, the coefficient of determination, and the t-test. The results of this study show that the influence of Instagram social media on the decision to stay has a significance value (Sig.) of 0.000, which is smaller than 0.05. This means that the regression model used in this study has a partial or valid effect, indicating that H1 is accepted. Thus, it can be concluded that Instagram social media has a positive and significant influence on the decision to stay at The Jayakarta Hotel Bali Beach & Resort.